The Subversions and Perversions of Shadow Vigilantism - Robinson, Paul H. (2018)
This excerpt from the recently published Shadow Vigilantes book argues that, while vigilantism, even moral vigilantism, can be dangerous to a society, the real danger is not of hordes of citizens, frustrated by the system’s doctrines of disillusionment, rising up to take the law into their own hands. Frustration can spark a vigilante impulse, but such classic aggressive vigilantism is not the typical response. More common is the expression of disillusionment in less brazen ways by a more surreptitious undermining and distortion of the operation of the criminal justice system. Shadow vigilantes, as they might be called, can affect the operation of the system in a host of important ways. For example, when people act as classic vigilantes or when people exceed the legal rules in their use of defensive force against apparent criminals, or when law enforcement officials exceed their authority in dealing with offenders, shadow vigilante citizens can refuse to report the crime or to help investigators, or they can refuse to indict as grand jurors or refuse to convict as trial jurors. Further, frustration with doctrines of disillusionment can lead politicians to urge legal reforms that seem to avoid failures of justice, but that also overreach and produce regular injustices. Shadow vigilantism can also be seen in the conduct of officials within the system who feel morally justified in subverting the system because they see it as regularly and indifferently producing failures of justice. Such subversion is apparent, for example, in officials refusing to prosecute vigilantes, police, or crime victims who stray beyond legal limitations when using force against aggressors. It’s also apparent in police “testilying” to subvert search and seizure technicalities (and judicial toleration of it) and in prosecutorial overcharging to compensate for past perceived justice failures